Optimization and Evaluation of 5‐Styryl‐Oxathiazol‐2‐one Mycobacterium tuberculosis Proteasome Inhibitors as Potential Antitubercular Agents. Issue 3 (17th April 2015) - Russo, Francesco; Gising, Johan; Åkerbladh, Linda; Roos, Annette K.; Naworyta, Agata; Mowbray, Sherry L.; Sokolowski, Anders; Henderson, Ian; Alling, Torey; Bailey, Mai A.; Files, Megan; Parish, Tanya; et al.
Abstract This is the first report of 5‐styryl‐oxathiazol‐2‐ones as inhibitors of the Mycobacterium tuberculosis (Mtb) proteasome. As part of the study, the structure–activity relationship of oxathiazolones as Mtb proteasome inhibitors has been investigated. Furthermore, the prepared compounds displayed a good selectivity profile for Mtb compared to the human proteasome. The 5‐styryl‐oxathiazol‐2‐one inhibitors identified showed little activity against replicating Mtb, but were rapidly bactericidal against nonreplicating bacteria. (E)‐5‐(4‐Chlorostyryl)‐1, 3, 4‐oxathiazol‐2‐one) was most effective, reducing the colony‐forming units (CFU)/mL below the detection limit in only seven days at all concentrations tested. The results suggest that this new class of Mtb proteasome inhibitors has the potential to be further developed into novel antitubercular agents for synergistic combination therapies with existing drugs.